Gene cloning and DNA analysis : an introduction - Brown, T. A. (Terence A.) (Wiley-Blackwell, 2021)
"The main development in DNA technology since publication of the Seventh Edition of Gene Cloning has been the increased use of gene editing as a tool in both research and biotechnology. The basic methodology for CRISPR editing is now described in Chapter 12 and the applications of the method are explored, in the context of plant genetic engineering, in Chapter 16. Elsewhere, the continuing evolution of next-generation DNA sequencing is reflected by a reorganization of this part of Chapter 10, and to deal with the further proliferation of methods for studying transcriptomes and proteomes (albeit not strictly DNA Analysis) I have created a new chapter devoted to these methods. Other additions include new sections on melt curve analysis of real-time PCR products and genetic typing of human disease mutations"--